Analysis of Financial Literacy and Financial Behavior Toward Investment Decisions on Millennial: Technological Advancement as A Moderating Variable (International Journal of Scientific Research and Management (IJSRM), 2024)
Technology is increasingly rapid in people’s lives, including in the fields of economics and business. Economic and business development cannot be separated from the role of technology. The increasingly rapid development of technology currently also spurs the irrational consumption behavior of some people, this situation has an impact on life. Therefore, a person’s financial literacy is needed in responding to these challenges, especially in financial management. It is hoped that technological advances can strengthen people’s financial literacy and financial behavior. The aims of this research is to examine the effect of financial literacy and financial behavior on investment decisions; examines the moderating role of technological advance on the influence of financial literacy and financial behavior on investment decisions. This research uses a quantitative approach, with convenience sampling techniques. This research uses primary data through a survey distributed online. The data analysis technique uses the Structural Equation Modeling (SEM) test. The research results show that financial literacy has no effect on investment decisions, while financial behavior has a positive effect on investment decisions. Then, technological advances can strengthen the influence of financial intelligence on investment decisions, while technological advances do not moderate the influence of financial behavior on investment decisions.